Experimental and numerical analysis of bolt-loaded open-hole laminates reinforced by winded carbon rovings. (1st May 2016) - Botzkowski, Tim; Galkin, Siegfried; Wagner, Sebastian; Sikora, Sebastian P.; Kärger, Luise
Abstract: Quasistatic and oscillating forces transferred into carbon composite parts by bolts are limited by poor bearing stresses. There are various approaches to reinforce open holes, for example by the use of integrated metal sheets or by complexly stitched rovings. In the present paper, the influence of a winded roving applied to a bolt-loaded open-hole laminate is investigated in terms of the structural responses. As basis of this research, a non-reinforced open-hole laminate as well as single winded carbon loops are regarded as reference samples. Both reference-laminate and reference single-loops are tested experimentally under bolt-loading to obtain load–displacement results, which are used to set simulation parameters and to validate corresponding finite element (FE) models. For numerical investigation, three-dimensional finite volume element models are generated to describe the carbon loops considering cross sections as well as ondulations of the fibre rovings. The influence of manufacturing effects on the roving's cross sections is considered and assessed. Based on these findings, an idealised model of the multi-loop reinforced open-hole laminate is set up. Subsequently, the accuracy of this analysis method is validated by experimental tests of a laminate reinforced by three loops.